Cultivating the Values of Communication Ethics in Madrasah - Munifah Munifah; Muhibbin Syah; Asep Saeful Muhtadi; Nanat Fatah Natsir (Riviera Publishing, 2024)
this study is motivated by the current symptoms of moral decline, such as poor communication occurs among vulnerable adolescents with emotional traits. Many facts in society prove that wrong or incorrect communication will give birth to various immoral behaviors, fights, brawls, and various negative things that arise due to communication that does not care about ethics. This study uses a qualitative approach with descriptive analytical methods. The method of data collection in this study used in-depth interviews and supported by observation and documentation data. The results of this study indicate that: planting the value of communication ethics in the four MTs Banjar has been done through polite, courtesies, and greetings, both inside and outside the madrasah. So that it becomes a daily habit with the aim to improve the morale, and mental learners but not maximal. Therefore, instilling an understanding of communication ethics to students is very important so that they know how good communication ethics when communicating in terms of behaving and speaking appropriately.